2019
DOI: 10.15171/ijpni.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic efficiency and in vitro growth of Celastrus paniculatus Willd. under varied concentrations of CO2

Abstract: Introduction: Celastrus paniculatus (family: Celastraceae) is a woody climbing shrub valued for its immense medicinal properties contained in its various plant parts. Over-exploitation and poor natural regeneration either by seed or other method/s have resulted into depleting population of C. paniculatus in natural habitats in India. Novel approaches such as liquid culture media and photoautotrophic multiplication of shoots on sugar-free media has proved useful to obtain photosynthetically active micropropagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…[30], Celastrus paniculatus Wall. [31] and Vernonia condensata Baker [32] supplemented with conventional sugar concentrations and allowed the growth of shoots cultured with low sucrose or even without any supplementary carbohydrate, as reported for Paulownia fortunei (Seem.) Hemsl.…”
Section: Discussionmentioning
confidence: 99%
“…[30], Celastrus paniculatus Wall. [31] and Vernonia condensata Baker [32] supplemented with conventional sugar concentrations and allowed the growth of shoots cultured with low sucrose or even without any supplementary carbohydrate, as reported for Paulownia fortunei (Seem.) Hemsl.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been confirmed that removal of the two main inputs of photosynthesis (light and CO 2 ) are detrimental for production of plants in vitro [6]. In accordance, CO 2 enrichment in vitro increased the shoot growth and multiplication rate in Celastrus paniculatus [14]. In the course of CO 2 starvation, all endogenous electron acceptors become reduced, leaving oxygen as the main available electron acceptor.…”
Section: Introductionmentioning
confidence: 95%